2001
DOI: 10.1081/lft-100000763
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Prolonged Deactivation-Regeneration Regimes on the Dehydrogenation Activity of Platinum/Alumina Catalyst

Abstract: The various types of coke found deposited on a deactivated Pt/Al 2 O 3 reforming catalyst are described. They are claSsified into major types: oxidiZable (primary) coke, reducible (secondary) coke and non oxidizable and non reducible (tertiary) coke. Primary coke is generally non toxic to catalytic hydrocarbon conversion as its removal restores initial catalyst activity. The secondary and tertiary forms are, however, toxic to this reaction. A methodology for the prolongation of reforming catalyst life is evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Developing a catalyst that can maintain high stability requires a deep understanding of the deactivation phenomena. Groups of researchers have investigated the deactivation of Pt/Al 2 O 3 catalysts in MCH dehydrogenation. Some studies suggested that catalyst deactivation in MCH dehydrogenation is caused by two types of poison structures: one reversible and the other irreversible. The reversible poison can be removed at normal operating temperature by a stream of pressurized hydrogen, whereas the irreversible poison cannot. The relative amount of each poison structure depends on the hydrogen partial pressure and the time “on-stream”.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Developing a catalyst that can maintain high stability requires a deep understanding of the deactivation phenomena. Groups of researchers have investigated the deactivation of Pt/Al 2 O 3 catalysts in MCH dehydrogenation. Some studies suggested that catalyst deactivation in MCH dehydrogenation is caused by two types of poison structures: one reversible and the other irreversible. The reversible poison can be removed at normal operating temperature by a stream of pressurized hydrogen, whereas the irreversible poison cannot. The relative amount of each poison structure depends on the hydrogen partial pressure and the time “on-stream”.…”
Section: Introductionmentioning
confidence: 99%
“…Groups of researchers have investigated the deactivation of Pt/Al 2 O 3 catalysts in MCH dehydrogenation. [1][2][3][4][5][6][7][8] Some studies suggested that catalyst deactivation in MCH dehydrogenation is caused by two types of poison structures: one reversible and the other irreversible. [2][3][4] The reversible poison can be removed at normal operating temperature by a stream of pressurized hydrogen, whereas the irreversible poison cannot.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 It is important to note that there have been many books, papers, and patents on coke deposition research as well as coke removal and surface regeneration from catalyst surfaces. [6][7][8][9][10][11] The objective of this study is to investigate and assess the practicality of various in situ surface regeneration techniques for realistic passage sizes and to develop a safe, simple, and cost-effective in situ surface regeneration technique for hydrocarbon fuel-cooled thermal management systems. Thermogravimetric analysis (TGA) was adopted in this study for quickly evaluating various coke-removal processes and compiling a database for kinetic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, UTRC has also shown that different elements (e.g., carbon and sulfur) are burned off at different temperatures and that further development of the regeneration process is required . It is important to note that there have been many books, papers, and patents on coke deposition research as well as coke removal and surface regeneration from catalyst surfaces. …”
Section: Introductionmentioning
confidence: 99%